2010
DOI: 10.1097/iop.0b013e3181b8efee
|View full text |Cite
|
Sign up to set email alerts
|

Myxofibrosarcoma of the Orbit: A Clinicopathologic Case Report

Abstract: A 27-year-old woman developed a rapidly progressive left orbital tumor which extended into the cranial fossa. MRI revealed a heterogenous enhancing lesion confined to the left frontal bone and superior orbit. An excisional biopsy was performed and examination of the specimen showed findings diagnostic of a high-grade0020myxofibrosarcoma. Myxofibrosarcoma is a fibroblast-derived soft tissue neoplasm with up to a 60% local recurrence rate and metastasis may be associated with intermediate to high grade tumors. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…9 Immunohistochemical analysis is usually negative for S-100, SMA, desmin, and cytokeratin; however, staining with vimentin is strong and diffuse. [9][10][11] Ultrastructurally, the tumor cells may show cytoplasmic vacuoles, prominent endoplasmic reticulum, well-developed Golgi apparatus, and moderate numbers of mitochondria. [9][10][11] On review of literature, it was found that MFS of the orbit is probably an underreported entity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Immunohistochemical analysis is usually negative for S-100, SMA, desmin, and cytokeratin; however, staining with vimentin is strong and diffuse. [9][10][11] Ultrastructurally, the tumor cells may show cytoplasmic vacuoles, prominent endoplasmic reticulum, well-developed Golgi apparatus, and moderate numbers of mitochondria. [9][10][11] On review of literature, it was found that MFS of the orbit is probably an underreported entity.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Ultrastructurally, the tumor cells may show cytoplasmic vacuoles, prominent endoplasmic reticulum, well-developed Golgi apparatus, and moderate numbers of mitochondria. [9][10][11] On review of literature, it was found that MFS of the orbit is probably an underreported entity. 9 It is believed that at least few of the orbital MFS could have been misdiagnosed as a malignant fibrous histiocytoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myxofibrosarcoma rarely occurs in the head and neck regions [1], and only a few corresponding cases in these areas have been reported, with 3% to 10% involvement, including the larynx [2], esophagus [3], sphenoid sinus [4,5], mandible [6], maxillary sinus [7], parotid [8,9], orbit [10,11], and infratemporal space [12]. To our knowledge, only one case has so far been reported regarding MFS generated from the hypopharynx [13].…”
Section: Introductionmentioning
confidence: 99%
“…MFS also portends a better prognosis than the variants of MFH [4,5,6,7]. MFS classically presents superficially in the lower extremities, followed by the trunk, upper extremities, neck, and head [1,8,9,10], but it has also been reported superficially in the breast [11,12], perineum [13], and orbit [14,15]. Reports also exist of MFS in deep sites, including the esophagus [16], hypopharynx [17], vocal fold [18], parotid [19], heart [20,21,22], aorta [23], pulmonary artery [24], lung [25] and brain [26,27].…”
Section: Introductionmentioning
confidence: 99%